INOVASI PEMBELAJARAN BERBASIS GOOGLE SITE: PELATIHAN PEMBUATAN BAHAN AJAR UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Khadijah, Khadijah; Ahmad Zaki; Nasir, Norma; Alimuddin, Fauziyyah; Ayu Rahayu (Education and Talent Development Center of Indonesia, 2025)
This activity was motivated by the limited ability of teachers to develop interactive and engaging digital teaching materials, which affects students’ independent learning skills. In today’s digital era, teachers are required not only to master the subject matter but also to utilize technology to support an independent and enjoyable learning process. The main objective of this activity was to provide training for teachers at Madrasah Aliyah Arifah Gowa in developing teaching materials through interactive online sites as an innovative learning approach to promote student autonomy. The implementation method consisted of three main stages: planning, execution, and evaluation. During the planning stage, training materials were prepared, covering the introduction of digital platforms, techniques for developing site-based teaching materials, and practical implementation guides. The execution stage was carried out through face-to-face training sessions combined with individual practice and intensive mentoring by the implementation team. The evaluation stage was conducted through assessment of the teaching products, reflective discussions, and participant satisfaction questionnaires. This activity involved a single group of 25 teachers from Madrasah Aliyah with diverse subject backgrounds. The results showed that all participants were able to create teaching materials using Google Sites that were attractive, easily accessible to students, and aligned with their respective subjects. The materials produced have been used as independent learning resources by students at their schools. The benefits gained include improved teacher competence in digital teaching material development, increased student motivation to learn independently, and the formation of a collaborative teacher network for developing learning media. This activity emphasizes that engaging teachers in practice-based training can drive digital transformation in education and strengthen the active role of the educational community in improving student learning quality.